2016
DOI: 10.1002/ece3.2020
|View full text |Cite
|
Sign up to set email alerts
|

Lateral plate number in low‐plated threespine stickleback: a study of plasticity and heritability

Abstract: In the threespine stickleback Gasterosteus aculeatus model system, phenotypes are often classified into three morphs according to lateral plate number. Morph identity has been shown to be largely genetically determined, but substantial within‐morph variation in plate number exists. In this study, we test whether plate number has a plastic component in response to salinity in the low‐plated morph using a split‐clutch experiment where families were split in two, one half raised in water at 0 and the other at 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Growth is also a plastic trait in the threespine stickleback (e.g. Mccairns and Bernatchez 2012), though plate morphotype (Colosimo et al 2005; Barrett et al 2008; Marchinko 2009) and number (Hansson et al 2016) are not. The effect demonstrated here represents a rare example of a phenotypic response to temperature change that is underpinned by genetic change.…”
Section: Discussionmentioning
confidence: 99%
“…Growth is also a plastic trait in the threespine stickleback (e.g. Mccairns and Bernatchez 2012), though plate morphotype (Colosimo et al 2005; Barrett et al 2008; Marchinko 2009) and number (Hansson et al 2016) are not. The effect demonstrated here represents a rare example of a phenotypic response to temperature change that is underpinned by genetic change.…”
Section: Discussionmentioning
confidence: 99%
“…), including stickleback plate number plastically responding to a change in salinity (Hansson et al. ). As such, it is possible that these or other environmental cues could be modulating the number of plates within plate morph, possibly along a reaction norm that is established by genotype ( EDA or otherwise) (Schlichting and Pigliucci ).…”
Section: Discussionmentioning
confidence: 99%
“…Plate phenotypes are clearly influenced strongly by EDA genotype (Colosimo et al 2005), but are also modified by other genes (Colosimo et al 2004). Additional modulators such as epigenetic modifications or phenotypic plasticity may also be important; indeed, it has been shown that phenotypic plasticity has a strong effect on stickleback morphology in response to different environmental cues (Day et al 1994;Wund et al 2008Wund et al , 2012Svanb€ ack and Schluter 2012;Lucek et al 2014;Mazzarella et al 2015), including stickleback plate number plastically responding to a change in salinity (Hansson et al 2016). As such, it is possible that these or other environmental cues could be modulating the number of plates within plate morph, possibly along a reaction norm that is established by genotype (EDA or otherwise) (Schlichting and Pigliucci 1998).…”
Section: The Genetic Basis Of Platelessness In Sticklebacksmentioning
confidence: 99%
“…Multiple genomic regions have been associated with adaptation to fresh water (Jones et al., 2012), with the ectodysplasin A locus specifically implicated in lateral plate evolution. The heritability of plate number is high (Hansson et al., 2016), with 70% of variation in plate number associated with variation in ectodysplasin A (Colosimo et al., 2005; Cresko et al., 2004). Marine populations are assumed to possess a pool of standing genetic variation, with rare variants of the ectodysplasin A locus experiencing strong selection once fish enter fresh water, where they rapidly increase in frequency (Barrett, 2010).…”
Section: Introductionmentioning
confidence: 99%